Конфікси об-…-ок, над-…-ок, від-…-ок та про-…-ок в українській мові (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article is dedicated to the ways of formation of structure and development of confixal derivatives with affixes об-…-ок, над-…-ок, від-…-ок and про-…-ок in the course of writing period of the Ukrainian language development.